Supportive and palliative care needs of families of children with life-threatening illnesses in Western Australia: evidence to guide the development of a palliative care service - Monterosso, Leanne; Kristjanson, Linda; Aoun, Samar; Phillips, M. (Sage Science Press (UK), 2007)
Objective: To obtain feedback from families of children receiving palliative and supportive care about their care needs in hospital and in community settings. Design: A two-phase combined quantitative and qualitative study. Setting: Western Australia. Participants: 134 parents and 20 service providers. Results: Analysis indicated the concept of palliative care is poorly understood by health professionals and by parents. Many families are affected emotionally, financially and physically by the burden of caring for children with life threatening or chronic conditions requiring complex care at home. Parents indicated the need for clear and honest information about their child's condition and prognosis throughout the trajectory of illness and perceived this had been lacking. Families required financial and practical assistance with providing care from their children at home. Parents also wanted more practical resources and information to assist with the management of their child's nutrition and pain, as well as support for their other children. The level of respite (in home and residential) was perceived to be insufficient and inequitable. Parents also required access to, and advice from, multidisciplinary health professionals when caring for their child at home. There was a perceived lack of coordination between community services and the hospital. Conclusion: Education of health professionals and parents regarding the concepts and introduction of palliative and supportive care is required. Care for children and their families should be coordinated by a multidisciplinary team in consultation with children and their families, and linked and integrated with the treating hospital in collaboration with community services. More inclusive criteria are required for community services including practical aids and respite care.